CRISPR/Cas12a with Universal crRNA for Indiscriminate Virus Detection - Zhenlin Shang; Sitong Liu; Dongxu Liu; Xiaojing Pei; Shujing Li; Yifan He; Yigang Tong; Guoqi Liu (Molecules)
Viruses, known for causing widespread biological harm and even extinction, pose significant challenges to public health. Virus detection is crucial for accurate disease diagnosis and preventing the spread of infections. Recently, the outstanding analytical performance of CRISPR/Cas biosensors has shown great potential and they have been considered as augmenting methods for reverse-transcription polymerase chain reaction (RT-PCR), which was the gold standard for nucleic acid detection. We herein utilized Cas12a with universal CRISPR RNA (crRNA) for indiscriminate virus detection by attaching the target to a longer track strand for isothermal amplification. The amplified products contain a domain that is recognized by the Cas12a/crRNA complex, triggering the cleavage of surrounding reporters to produce signals, thereby escaping the target dependence of crRNA recognition. The proposed method allows the same crRNA to detect multiple viral nucleic acids with high sensitivity, including but not limited to SARS-CoV-2, human papillomaviruses (HPV), HCOV-NL63, HCOV-HKU1, and miRNA biomarkers. Taking SARS-CoV-2 and HPV16 pseudoviruses as examples, this method was proved as a versatile and sensitive platform for molecular diagnostic applications.